Lung Sarcoidosis in Etanercept Treated Rheumatoid Arthritis Patient: A Case Report and Review of the Literature - Supat Thongpooswan; Adriana Abrudescu (Case Reports in Rheumatology)
We report a 55-year-old female with seropositive rheumatoid arthritis for 10 years who developed large mediastinal and hilar adenopathy while receiving etanercept therapy. Chest high resolution computed tomography (HRCT) showed mediastinal lymph nodes with size of 2.3×3.1 centimeters. Right paratracheal lymph node biopsy showed nonnecrotizing epithelioid granulomata. All infectious studies of pulmonary lymph node tissues were negative. Etanercept was discontinued. Follow-up HRCT 6 months later showed resolution of mediastinal lymph nodes. This report should increase awareness of pulmonary sarcoidosis development in patient treated with tumor necrosis factor-alpha blocking agent, etanercept.